The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/124851
|View full text |Cite
|
Sign up to set email alerts
|

Species Turnover across Different Life Stages from Seedlings to Canopy Trees in Swamp Forests of Central Brazil

Abstract: Processes driving the assembly of swamp forest communities have been poorly explored. We analyzed natural regeneration and adult tree communities data of a swamp gallery forest in Central Brazil to discuss the role of ecological filters in shaping plant species turnover in a successional gradient. Species data of 120 plots were used to assess species turnover between natural regeneration and adult tree communities. Our analyses were based on 4995 individuals belonging to 72 species. Community patterns were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Flooded and non‐flooded gallery forests of the Cerrado differ in soil properties, nutrient cycling, tree dynamics, structure, and floristic composition (Fontes et al., 2015; Ivanauskas et al., 1997; Naiman & Décamps, 1997; Ribeiro & Walter, 2008; Silva et al., 2013; Silver et al., 1999). Seasonally or permanently flooded gallery forests have higher tree density, but lower tree dominance and species richness than non‐flooded gallery forests (Ribeiro & Walter, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flooded and non‐flooded gallery forests of the Cerrado differ in soil properties, nutrient cycling, tree dynamics, structure, and floristic composition (Fontes et al., 2015; Ivanauskas et al., 1997; Naiman & Décamps, 1997; Ribeiro & Walter, 2008; Silva et al., 2013; Silver et al., 1999). Seasonally or permanently flooded gallery forests have higher tree density, but lower tree dominance and species richness than non‐flooded gallery forests (Ribeiro & Walter, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies performed on the epiphyte flora of the Cerrado showed that diverse epiphyte communities were restricted to gallery forests (Felfili et al, 2001;Ribeiro & Walter, 2008). Epiphytes correspond to only 4% (69 species) of the spermatophytes (seed-bearing plants) in Cerrado gallery forests (Felfili et al, 2001), but local abundance can be substantial: Oliveira Flooded and non-flooded gallery forests of the Cerrado differ in soil properties, nutrient cycling, tree dynamics, structure, and floristic composition (Fontes et al, 2015;Ivanauskas et al, 1997;Naiman & Décamps, 1997;Ribeiro & Walter, 2008;Silva et al, 2013;Silver et al, 1999). Seasonally or permanently flooded gallery forests have higher tree density, but lower tree dominance and species richness than non-flooded gallery forests (Ribeiro & Walter, 2008).…”
mentioning
confidence: 99%
“…The number of species of seedlings and saplings in Tanah Merah Coast area did not differ significantly (see Table 1 and Table 2), while at the Samboja Reservoir area significantly differed. The research conducted by Fontes et al (2015) reveals that once plants start to grow and become sapling, the floristic composition of forest changes remarkably. This shift in floristic composition suggests that soil waterlog may act as a strong abiotic filter in the assembly of juvenile and adult communities.…”
Section: Species Compositionmentioning
confidence: 99%